Hospitalised ocular injuries in Osogbo, Nigeria - Olubayo Umar Kolawole (Guoji Yanke Zazhi, 2015)
AIM: To describe the epidemiology and outcome of ocular injuries requiring hospital admission in Ladoke Akintola University of Technology Teaching Hospital(LTH), Osogbo, Nigeria. METHODS: Retrospective chart review of all patients hospitalized for ocular injuries at LTH, Osogbo between April 2002 and March 2014 was undertaken. Information extracted from patients records were entered into a pre-designed form. Data were analyzed with Statistical Package for Social Sciences(SPSS)version 20. Logistic regression analysis was used to assess effects of different variables on the visual outcome of ocular injuries after treatment among the subjects. P<0.05 was used as test of statistical significance. RESULTS: One hundred and twenty-seven patients were hospitalized at LTH within the study period. The median age was 22.0y(range: 0.5-70.0)and male: female ratio 2.6:1. Majority of the injuries(35.2%)occurred within the home setting. Of the 127 patients, 74(58.3%)had open globe Injuries(OGI), 34(26.8%)had closed globe injuries(CGI), 7(5.5%)had adnexal injuries, 6(4.7%)had ruptured globes, 4(3.1%)had chemical injuries, 1(0.8%)patient each had retained intraocular foreign body and thermal eye injury. Two-thirds of patients managed for ocular injuries in this series had poor visual outcome. There were statistically significant associations between poor initial visual acuity(OR=13.24)and OGI with poor visual outcome(OR=9.16). CONCLUSION: There is an urgent need for health education and, to put in place preventive strategies for ocular injuries. Developing countries need to build up capacity to offer complex anterior and posterior segment surgeries for those with severely injured eyes so as to improve the visual outcomes.